Water quality and heavy metal monitoring in water, sediments, and tissues of Corbicula sp. from Bung Boraphet reservoir, Thailand - Tinnapan Netpae (2018)
Bung Boraphet is the largest fresh water reservoir in Thailand. The accumulations of copper (Cu) and lead (Pb) in water, sediment and tissues of Asian clams (Corbicula sp.) within Bung Boraphet were carried out to indicate possible polluting effect of soil erosion and the dissolution of water soluble salts from Nan river. Samples were collected from 12 study sites within Bung Boraphet between February to December 2008. The physicochemical parameters of water including temperature, pH, turbidity, ammonia nitrogen, nitrate nitrogen, orthophosphates, biochemical oxygen demand, dissolved oxygen, Cu, and Pb were measured. In comparison with the surface water quality standard of Thailand, water in Bung Boraphet was medium clean. Cu and Pb in water were found at low levels but the heavy metals were detected at high levels in the sediment and tissues of Corbicula sp.